Efektivitas Media Online Terhadap Pemasaran Produk Usaha Kecil Menengah Bidang Kuliner Di Kecamatan Sario Kota Manado - Nur’Ain Naki; Rine Kaunang; Martha Marejke Sendow (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the effectiveness of online media on the marketing of small and medium business products in the culinary field in Sario District, Manado City. The data used in this study are primary data and secondary data. Primary data was obtained through direct interviews in the field using a questionnaire to owners of small and medium enterprises (SMEs) who are working in the culinary field. Secondary data is data obtained from the second source of the required data. The number of respondents in this study were 20 SME owners in the culinary field in Sario District, Manado City. The data were analyzed using an interactive model data analysis technique consisting of four components of the analysis process, namely data collection, data reduction, data display and drawing conclusions. Based on the results of the research, it was found that with the existence of online media, sales of small and medium businesses in Sario District are very effective for owners. It can be seen from the increase in sales ranging from 30% to 60%. The online media used are facebook, whatsapp, instagram, gofood, grabfood, shopeefood and maxim food and goods.